THE PREVALENCE OF ABDOMINAL OBESITY IN MEN OF AN OPEN URBAN POPULATION - M. M. Kayumova; E. I. Gakova; T. Y. Gorbunova; M. Y. Akimov (Сибирский научный медицинский журнал, 2019)
The World Health Organization recognized the overweight as the new non-infectious “epidemic of the XXI century”. By the beginning of the century, almost all countries in the world reported an increase in the prevalence of overweight, with over 400 million adults suffering from obesity and a further increase in its prevalence. The aim of the study was to determine the levels and prevalence of abdominal obesity in accordance with different criteria for assessing the able-bodied age of an open population of a medium-urbanized Siberian city in men. Material and methods. A one-time epidemiological study was conducted on a representative sample, formed from the electoral lists of male members aged 25-64 years in one of the administrative districts of Tyumen. For the analysis of the abdominal obesity, the criteria of the metabolic syndrome of International Diabetes Federation (IDF, 2005), National Cholesterol Education Program Expert Panel, Adult Treatment Panel III (NCEP ATP III, 2004), All-Russian Scientific Society of 2009) were used. Results and discussion. There was a directed age trend in the waist circumference with a significant increase in the AW levels in each subsequent age group by the levels of the central (abdominal) type of obesity in the Tyumen population. The standardized prevalence rate of abdominal obesity in the male population of 25-64 years in Tyumen was 42.6 % according to the IDF criteria, 17.9 % according to the NCEP ATP III criteria, 38.8 % according to the criteria of the VNOK, positive criteria were established for all criteria with age in the younger and older age categories. The results of this study can serve as a scientific base and starting point for the formation of comprehensive preventive programs among men of working age in Tyumen and other urbanized Russian cities.